Capillary electrophoresis determination of pravastatin and separation of Its degradation products - Nigović, Biljana (Array, 2008)
Abstract: A capillary zone electrophoresis method for pravastatin determination was developed and validated. Rapid migration of negatively charged pravastatin molecule was obtained in alkaline buffer by the application of electric field of 30 kV. Influence of the pH value and ionic strength of running buffer, applied voltage and capillary temperature on mobility and sensitivity was evaluated. Detection wavelength was set to 237 nm. The method was applied to the determination of the drug in pharmaceutical dosage form. Pravastatin is a δ-hydroxy acid, which is prone to lactonize and epimerize in a pH-dependent manner. Micellar electrokinetic chromatographic approach was chosen to develop a method able to separate pravastatin and its degradation products in acidic media. The proposed method allows baseline separation of hydroxy acid and neutral lactone forms of the drug that appear as interconversion products depending on the pH value